African hosts & their guests cultural dynamics of tourism - Beek, Wouter E. A. van 1943-; Schmidt, A. M. 1967- (James Currey, 2012)
Tourism is important for Africa: international tourist arrivals to Africa continue to grow, income from tourism is crucial to national economies, and tourism investments are considered among the most profitable. This edited volume deals with the interaction of local communities with tourists coming into their areas and villages. Based upon a common theoretical approach, fourteen cases of African tourism are discussed which involve direct contact between 'hosts' and 'guests'. The viewpoint throughout is from the side of the locals, establishing how the processes of interaction shape each small scale destination. Crucial in Africa is the fact that the large majority of tourism is game oriented and the interaction between locals and visitors is very much 'tainted' by this fact. Central is the notion of the tourist bubble - the infrastructure that is generated locally (and internationally) for hosting tourists, as it is this institutional interface that tends to impact on the local society and culture, not the tourists themselves directly. The examples come from all over Africa, from the Sahara to the Eastern Cape, and from Kenya to Ghana. All contributions are based upon original fieldwork. Walter van Beek is professor of anthropology at Tilburg University and Senior Researcher at the African Studies Centre, Leiden; Annette Schmidt is curator of the African department at the National Museum of Ethnology in Leiden, and is an archaeologist with a long experience in cultural management projects
James Currey is an imprint of Boydell & Brewer Ltd
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Tourism / Africa; Tourists / Africa; Tourismus; Kultursoziologe; Afrika; Aufsatzsammlung